Anti-Gal and Anti-Neu5Gc Responses in Nonimmunosuppressed Patients After Treatment With Rabbit Antithymocyte Polyclonal IgGs. Issue 10 (October 2017) - Salama, Apolline; Evanno, Gwénaëlle; Lim, Noha; Rousse, Juliette; Le Berre, Ludmilla; Nicot, Arnaud; Bach, Jean-Marie; Brouard, Sophie; Harris, Kristina M.; Ehlers, Mario R.; Gitelman, Stephen E.; Soulillou, Jean-Paul
Abstract : Background: Polyclonal antihuman thymocyte rabbit IgGs (antithymocyte globulin [ATG]) are popular immunosuppressive drugs used to prevent or treat organ or bone-marrow allograft rejection, graft versus host disease, and autoimmune diseases. However, animal-derived glycoproteins are also strongly immunogenic and rabbit ATG induces serum sickness disease in almost all patients without additional immunosuppressive drugs, as seen in the Study of Thymoglobulin to arrest Type 1 Diabetes (START) trial of ATG therapy in new-onset type 1 diabetes. Methods: Using enzyme-linked immunosorbent assay, we analyzed serial sera from the START study to decipher the various anti-ATG specificities developed by the patients in this study: antitotal ATG, but also antigalactose-α1-3-galactose (Gal) and anti-Neu5Gc antibodies, 2 xenocarbohydrate epitopes present on rabbit IgG glycans and lacking in humans. Results: We show that diabetic patients have substantial levels of preexisting antibodies of the 3 specificities, before infusion, but of similar levels as healthy individuals. ATG treatment resulted in highly significant increases of both IgM (for anti-ATG and anti-Neu5Gc) and IgG (for anti-ATG, -Gal, and -Neu5Gc), peaking at 1 month and still detectable 1 year postinfusion. Conclusions: Treatment with rabbit polyclonal IgGs in the absence of additional immunosuppression results in a vigorous response against Gal and Neu5Gc epitopes, contributing to an inflammatory environment that may compromise the efficacy of ATG therapy. The results also suggest using IgGs lacking these major xenoantigens may improve safety and efficacy of ATG treatment. Abstract : In patients without additional immunosuppression, polyclonal rabbit anti-lymphocyte globulins induce a vigorous IgM and IgG response against galactose-α1-3-galactose and Neu5Gc, peaking at 1 month and still detectable at 1-year postinfusion. Supplemental digital content is available in the text.